Optimization of operation of the Mindanao power system - Lopez, Patricia L. (1987)
Basically, the Mindanao Power System is a water resource system because it is dominated by hydro plants. The operation of the reservoirs, of these plants, determines, the ability of the grid to deliver the energy required by its consumers at a cost that is efficient to its owner, in this case, the Government. In other words, system operation is equated to the management of these reservoirs. The effectivity of management is reflected in the absence of power failures resulting from low inflow and depleted reservoirs. Since inflow is an unknown quantity in the reservoir management, there is a need to plan for the reservoir releases which will affect the operation of the system. In recent years too much emphasis has been placed in the developmental planning of generation projects. Equally important however, is the planning for operation which aims for the efficient utilization of the system's energy resources, to minimize cost of operation, without sacrificing the ability of the system to deliver energy, at an acceptable degree of reliability. The ultimate goal of operations planning is optimization of all the reservoirs in the system on real time. Before a short term or real time optimization is achieved however, the long/middle term targets should be established to serve as inputs on the real time analysis. Thus, a logical step by step process shown as Fig. 19 and recommended in Chapter IX is necessary for a comprehensive approach to system optimization. This work is a first step towards the development of a real time optimization model of the Mindanao System and thus is centered on a long/middle term optimization analysis. The long/middle term optimization model developed, utilized an operations research method called the Dynamic Programming Successive Approximation (DPSA) technique. The objective function is the use of water from the reservoirs of the existing hydro plants to satisfy energy system requirements with the view to minimizing operating system cost through the minimum usage of the standby diesel plans over a 52-week or one-year period. The reliability criteria is expressed in monetary terms as Penalty if the reservoir is not able to meet end level targets. The result of the optimization process is an optimum policy - a schedule of releases with their corresponding reservoir levels which could serve as targets for future work on short term optimization. The study of the results will also provide an insight on system needs. The optimum policy is tested for reliability using a simulation software program (HEC-3) already available in NAPOCOR.
The mathematical model was translated into a computer program which is able to run on VAX-11, a computer available in NAPOCOR. TO test the model evolved, optimization was made here of the Mindanao Power System using the available historical inflow data converted into weekly series. Three typical or normal hydrological conditions (dry, average, wet) were used to test the behavior of the model developed. The analysis was made at a future year, (1995) and assumed the 1985 Mindanao Generation Expansion Plans to be in effect. These inputs however, can be altered depending on the particular year that is being considered. For example, a forecast of inflow should be used instead of a historical series. THe results of the analysis established generally that the optimization of the Mindanao system on a long/middle term could be done by the DPSA method. The system conditions of the grid in 1995 however was found to be inadequate in terms of meeting future demand. This is evidenced by the non-recovery of the optimum trajectories of the reservoirs whatever hydrological condition was used. The results of the simulation by HEC using a 55-year historical series had also confirmed these conclusions. The optimization established the fact that Agus I is the most important reservoir to be optimized, with the other reservoirs not registering definite patterns of releases, implying these reservoirs to be good only for short term regulation. Further refinements as suggested could be made of the model, and concurrently, optimization studies on real time could be carried out utilizing the same model but with some recommended changes. THe subsequent text is divided into nine (9) Chapters - from the Background down to the Recommendations. It is then followed by the References, Figures and the Appendix. The latter contains a collection of terms repeatedly used in the text and were thus defined for reference. These terms were italicized in the main text. The historical inflow data, optimization program, flow chart, input and output runs made are also included in the Appendix. The output, however includes only those at the final iteration for the optimization and only the three (3) years considered as dry, average, and wet year cases, not the full 55-year series for the HEC simulation.
Thesis (M.S.)--University of the Philippines, Diliman.
Typescript.
Keywords: Hydroelectric power plants -- Philippines -- Mindanao; Mathematical optimization; Reservoirs -- Philippines -- Mindanao